2014
DOI: 10.5732/cjc.013.10137
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict Gleason sum upgrading of clinically diagnosed localized prostate cancer among Chinese patients

Abstract: Although several models have been developed to predict the probability of Gleason sum upgrading between biopsy and radical prostatectomy specimens, most of these models are restricted to prostate-specific antigen screening-detected prostate cancer. This study aimed to build a nomogram for the prediction of Gleason sum upgrading in clinically diagnosed prostate cancer. The study cohort comprised 269 Chinese prostate cancer patients who underwent prostate biopsy with a minimum of 10 cores and were subsequently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Significant differences were found between the 2 groups (p < 0.001). Consistent with a previous study, Wang et al [23] demonstrated that Gleason sum upgrading in patients with low or intermediate-grade disease was significant. When applied to this subgroup, our correct system showed satisfactory discrimination and application.…”
Section: Discussionsupporting
confidence: 81%
“…Significant differences were found between the 2 groups (p < 0.001). Consistent with a previous study, Wang et al [23] demonstrated that Gleason sum upgrading in patients with low or intermediate-grade disease was significant. When applied to this subgroup, our correct system showed satisfactory discrimination and application.…”
Section: Discussionsupporting
confidence: 81%
“…Clinical T-stage is an important variable as for predicting prognosis and guiding treatment decisions. It is also predictive for Gleason upgrade found in several studies [4,[8][9][10]12] . It is acknowledged that advanced T stage is correlated with large tumor volume, which could bring di culties in sampling small Gleason patterns.…”
Section: Discussionmentioning
confidence: 62%
“…PSA is a widely used indicator for risk strati cation and different outcomes in PCa. As for predicting GS change, PSA might also play a role [4][5][6][7][8][9][10][11][12] . In current study, we found that PSA was also predictive and increased PSA was strongly correlated with GSU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, internal validation, such as cross-validation and bootstrap resampling, has a theoretical probability of overinterpretation [9]. Therefore, external validation is more appropriate for examining the model applicability, e.g., using a data set from other institutions or a validation set by the data-splitting method from the same institution, especially when the sample size is large [7, 13]. In this study, we calibrated the nomogram with a validation set and an IMRT cohort from the same institution that were independent from the training set.…”
Section: Discussionmentioning
confidence: 99%